Prognostic Value of BRAF Mutation in Glioblastoma - Ayesha Sohail; Qurat-Ul-Ain Virani; Hafiza Fatima Aziz; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
With advances in molecular genetics, exploring targetable mutations for treating glioblastoma (GBM) patients, has become a centre of interest in modern day neuropathology. BRAF mutation has been extensively reported in several brain tumours. Recent studies report identification of BRAF mutation in GBM patients, especially isocitrate dehydrogenase wildtype glioblastomas (IDH-WT GBM), and its potential role in patient outcomes. Here we discuss the existing literature on the prognostic value of BRAF mutation in GBM. Keywords: Glioblastoma, BRAF mutation, prognosis